ORIGIN OF COMPACT TYPE A REFRACTORY INCLUSIONS FROM CV3 CARBONACEOUS CHONDRITES - GROWTH BY INCORPORATION - Simon S.B.; Davis A.M.; Grossman L. (My University, 1999)
Compact type A (CTA) inclusions are one of the major types of coarse-grained refractory inclusions found in carbonaceous chondrites. They have not been studied in a systematic fashion, leading to some uncertainties and unproven assumptions about their origin. To address this situation, we studied a total of eight CTAs from Allende, Efremovka and Axtell by scanning electron-microscopic and electron and ion-microprobe techniques. These inclusions are very melilite-rich, ranging from ~60 vol% to nearly monomineralic. Also present are Mg-Al spinel (5-20%), perovskite (trace-~3%) and, in some samples, Ti-rich (~17 wt% TiO2t°t) fassaite (trace-~20%), and rhonite (=<1%). Melilite compositions are mostly between #9k15 and #9k40. Chondrite-normalized REE abundance patterns for melilite (flat at ~10 x CI with positive Eu anomalies) and fassaite (slight HREE enrichment relative to LREE and negative Eu anomalies) are like those for their counterparts in once-molten type B inclusions. The patterns for rhonite have positive slopes from La through Lu and abundances <10 x CI for La and 35-60 x CI for Lu. Features of CTAs that suggest that they were once molten include: rounded inclusion shapes; positively correlated Sc and V abundances in fassaite; radially oriented melilite laths at inclusion rims; and the distribution of trace elements among the phases. Fractional crystallization models show that, with one exception, the REE contents of perovskite and fassaite arose by crystallization of these phases from late, residual liquids that would have resulted from prior crystallization of the observed proportions of melilite and spinel from liquids having the bulk compositions of the inclusions. One Allende CTA (TS32), however, has several features (irregular shape, reversely zoned melilite, fassaite REE contents) that are not readily explained by crystallization from a melt. This inclusion may have undergone little melting and may be dominated by relict grains.